Charabanc, cultural capital and the men of recognised credit - Brenda Winter (Ilha do Desterro)
This paper compares the cultural legacy of the all-female Charabanc with that of Field Day, its fellow counterpart in the Irish Theatre touring movement in the 1980s. It suggests that a conscious awareness amongst the all-male Field Day board of successful writers and directors of what Bourdieu has called 'cultural capital' is implicated in the enduring authority of the work of that company within the history of Irish theatre. Conversely the paper considers if the populist Charabanc, in its steadfast refusal to engage with the hierarchies of academia and publishing, was too neglectful of the cultural capital which it accrued in      its heyday and has thus been party to its own occlusion from that same history.